2008
DOI: 10.1007/s11104-008-9550-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of irrigating dairy-grazed grassland with farm dairy effluent on nitrous oxide emissions

Abstract: While irrigation of farm dairy effluent (FDE) to land is becoming popular in New Zealand, it can lead to increased emissions of the greenhouse gas nitrous oxide (N 2 O). This paper reports the results from trials on N 2 O emissions from irrigation of FDE to two dairy-grazed pastures on two poorly drained siltloam soils located at Waikato and Manawatu, New Zealand. These pasture soils were periodically irrigated with FDE under contrasting soil moisture conditions with water-filled pore-space (WFPS) ranging betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 35 publications
1
27
0
Order By: Relevance
“…Luo et al (2008) reported up to 45% reduction in N 2 O emissions from dairy cow urine applied to various soils in New Zealand by the dicyandiamide nitrification inhibitor (DCD). The effectiveness of the DCD nitrification inhibitors depends largely on temperature, moisture and soil type (Kelliher et al, 2008;de Klein and Monaghan, 2011;Schils et al, 2013).…”
Section: Manure Applicationmentioning
confidence: 99%
“…Luo et al (2008) reported up to 45% reduction in N 2 O emissions from dairy cow urine applied to various soils in New Zealand by the dicyandiamide nitrification inhibitor (DCD). The effectiveness of the DCD nitrification inhibitors depends largely on temperature, moisture and soil type (Kelliher et al, 2008;de Klein and Monaghan, 2011;Schils et al, 2013).…”
Section: Manure Applicationmentioning
confidence: 99%
“…Studies (e.g. Smith et al, 2003;Luo et al, 2008aLuo et al, , 2008bLuo et al, and 2008c have shown that soil WFPS, of all measured factors, has the strongest influence on N 2 O emissions from excretal N input. Generally, N 2 O emissions are greatest when soil WFPS is at or above soil field capacity.…”
Section: N 2 O Emissionsmentioning
confidence: 99%
“…Animal (2015), 9:3, pp 534-543 © The Animal Consortium 2014 doi:10.1017/S1751731114002742 animal 534 N 2 O emissions are generally higher in winter when soils are wet, and after grazing owing to the large amount of nitrogen (N) excreted in dung and urine (Luo et al, 2008b and2008c; Schills et al, 2013). Forage brassicas (Brassica spp.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher denitrification losses were found following cattle slurry injection compared to surface application to a grassland soil [15]. Liquid-waste injections have been shown to promote conditions conducive to denitrification by creating an anaerobic environment abundant in inorganic N and readily oxidizable C. Luo et al [18] studied the effects of irrigating dairy-grazed grassland with FDE on N 2 O emissions and observed that FDE irrigation increased N 2 O emissions compared to the control and varied with changes in climatic conditions and soil WFPS. The N 2 O emissions increased slightly after application of FDE, reaching a peak value soon after application in both early autumn 2004 and late summer 2005.…”
Section: Nitrous Oxide Emissionmentioning
confidence: 99%